Child labor bans, employment, and school attendance: Evidence from changes in the minimum working age - Mireille Kozhaya; Fernanda Martinez Flores (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
This paper investigates the effect of a unique child labor ban regulation on employment and school enrollment. The ban implemented in Mexico in 2015, increased the minimum working age from 14 to 15, introduced restrictions to employ underage individuals, and imposed penalties for the violation of the law. Our identification strategy relies on a DiD approach that exploits the date of birth as a natural cutoff to assign individuals into treatment and control groups. The ban led to a decrease in the probability to work by 1.2 percentage points and an increase in the probability of being enrolled in school by 2.2 percentage points for the treatment group. These results are driven by a reduction in employment in paid activities, and in the secondary and tertiary sectors. The effects are persistent several years after the ban. – – Dieses Papier untersucht die Auswirkungen eines Verbots von Kinderarbeit in Mexiko auf die Wahrscheinlichkeiten der Einschulung und Beschäftigung von Kindern. Das 2015 eingeführte Verbot hob das Mindestalter für die Ausübung von Erwerbstätigkeiten von 14 auf 15 Jahre an, führte Beschränkungen für die Beschäftigung Minderjähriger ein und setzte Strafen für Missachtungen dieser Regeln fest. Die Identifizierungsstrategie basiert auf einem DiD-Ansatz für den Behandlungs- und Kontrollgruppen anhand des Geburtsdatums gebildet werden. Die Ergebnisse zeigen, dass das Verbot von Kinderarbeit die Wahrscheinlichkeit zu arbeiten um 1,2 Prozentpunkte reduzierte und die Wahrscheinlichkeit eines Schulbesuchs um 2,2 Prozentpunkte erhöhte. Insbesondere sank die Ausübung von bezahlten Tätigkeiten sowie im sekundären und tertiären Sektor. Diese Effekte sind auch noch mehrere Jahre nach Einführung des Verbots von Kinderarbeit festzustellen.
Keywords: I38; J22; J23; J82; O12; 330; Child labor; ban; minimum working age; schooling